Rancang Bangun Alat Inkubator Sebagai Media Untuk Pengontrol Suhu Fermentasi Susu Sapi - Sari, Kholifatul Mayang; Agatha Hannabel Avnanta Puteri; Dinda Asmiyah Salsabila; Zaim As’ad; Surya Saputra Penangsang; Angga Dutahatmaja (Yayasan Cendekia Gagayunan Indonesia, 2025)
This community service program is carried out as a form of student service to the community, with a focus on increasing the added value of livestock products through appropriate technological innovations. Fermentation of cow's milk into yogurt requires proper temperature control to produce quality products. The purpose of this program is to design and build an automatic incubator tool that is able to control the temperature stably during the fermentation process, so as to improve the quality and safety of dairy products. The methods used include field studies, microcontroller-based system design, prototyping, and direct trials with community partners. The result of this activity is the creation of a simple incubator prototype with an automatic temperature control system using a temperature sensor and heater that can maintain the ideal fermentation temperature in the range of 41-43°C. The implication of this activity is an increase in the production capacity of processed fermented milk in a hygienic and sustainable manner, as well as community empowerment in the utilization of appropriate technology that is easy to operate and apply at the household and MSME scale. This program aims to be a practical solution for rural milk-producing areas.